Relationship between arterial stiffness and variability of home blood pressure monitoring. Issue 30 (24th July 2020) - Park, Jin-Sun; Shin, Joon-Han; Park, Jeong-Bae; Choi, Dong-Ju; Youn, Ho-Joong; Park, Chang-Gyu; Kwan, Jun; Ahn, Youngkeun; Kim, Dong-Woon; Rim, Se-Joong; Park, Seung-Woo; Sung, Jidong; et al.
Abstract : Abstract: Variability of blood pressure (BP) is known as a prognostic value for the subsequent target organ damage in hypertensive patients. Arterial stiffness is a risk factor for cardiovascular morbidity and mortality. The relationship between the arterial stiffness and the BP variability has been controversial. The objective of the present study was to investigate the relationship between arterial stiffness and home BP variability in patients with high normal BP and new onset hypertension (HTN). Four hundred sixty three patients (252 males, 49 ± 12 year-old) with high normal BP or HTN were enrolled. Using radial applanation tonometry, pulse wave analysis (PWA) was performed for evaluation of systemic arterial stiffness. All patients underwent both home BP monitoring (HBPM) and PWA. Home BP variability was calculated as the standard deviation (SD) of 7 measurements of HBPM. Multiple linear regression analysis was performed to estimate and test the independent effects of home BP variability on the arterial stiffness. Mutivariate analysis showed that both systolic and diastolic morning BP variabilities were correlated with arterial stiffness expressed as augmentation pressure (AP, β-coefficient = 1.622, P  = .01 and β-coefficient = 1.07, P  = .035). The SDs of systolic and diastolic BP of evening were also associated with AP (β-coefficient = 1.843, P  = .001 and β-coefficient = 1.088, P  = .036). The SDs of morning and evening systolic BP were associated with augmentation index (AI, β-coefficient = 1.583, P  = .02 and β-coefficient = 1.792, P  = .001) and heart rate (75 bpm) adjusted AI (β-coefficient = 1.592, P  = .001 and β-coefficient = 1.792, P  = .001). In present study, the variability of systolic BP was closely related with arterial stiffness. The home BP variability might be important indicator of arterial stiffness.